Influence of ion structure on thermal runaway behaviour of aprotic and protic ionic liquids. Issue 79 (3rd September 2020) - Vijayaraghavan, R.; Kar, Mega; Sivanesh, N. E.; Samuel, V. J.; Surianarayanan, M.; Olsen, Seth; MacFarlane, D. R.
Abstract : Accelerated rate calorimetry has been employed to study the exothermic and thermal runaway behaviour of some aprotic and protic ionic liquids. The aprotic [FSI] − salts are found to be more vulnerable to exothermic decomposition. Abstract : Accelerated rate calorimetric studies have been employed to study the exothermic and thermal runaway behaviour of some aprotic and protic ionic liquids based on several families of ions including the bis(flurorsulfonyl)imide anion ([FSI] − ); it was found that the protic salts are safer than aprotic salts of the [FSI] − anion.